A Review on the Role of the Neuroscience of Flow States in the Modern World - Gold, Joshua; Ciorciari, Joseph (Behavioral sciences, 2020)
Flow states have been shown to help people reach peak performance, yet this elusive state is not easily attained. The review describes the current state of literature on flow by addressing the environmental influences as well as the cognitive and neurocognitive elements that underlie the experience. In particular, the research focusses on the transition of cognitive control from an explicit to an implicit process. This is further expanded upon to look at the current, yet related neurocognitive research of high performance associated with the implicit process of automaticity. Finally, the review focusses on transcranial direct current stimulation (tDCS) as a novel method to facilitates an induction of flow states. Implications are aimed at a general technique to improve on skill acquisition and overall performance.